2019
DOI: 10.3389/fnins.2019.01133
|View full text |Cite
|
Sign up to set email alerts
|

The Delta-Subunit Selective GABAA Receptor Modulator, DS2, Improves Stroke Recovery via an Anti-inflammatory Mechanism

Abstract: Inflammatory processes are known to contribute to tissue damage in the central nervous system (CNS) across a broad range of neurological conditions, including stroke. Gamma amino butyric acid (GABA), the main inhibitory neurotransmitter in the CNS, has been implicated in modulating peripheral immune responses by acting on GABAA receptors on antigen-presenting cells and lymphocytes. Here, we investigated the effects and mechanism of action of the delta-selective compound, DS2, to improve stroke recovery and mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 73 publications
(123 reference statements)
0
14
0
Order By: Relevance
“…1 a, b). Upregulating IL-17 expression indicates a poorer treatment effect and prognosis 5 and decreased IL-17 is relative to improved motor function in mice 6,7 . Administration of IL-17A can nullify the microglial M2 polarization to inhibit anti-inflammation activity 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 a, b). Upregulating IL-17 expression indicates a poorer treatment effect and prognosis 5 and decreased IL-17 is relative to improved motor function in mice 6,7 . Administration of IL-17A can nullify the microglial M2 polarization to inhibit anti-inflammation activity 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-17 (IL-17, also called IL-17A), a proinflammatory cytokine mainly derived from γδ T cells and T helper 17 (Th17) cells, also has an important role in a wide variety of neurological diseases 4 . It has been found that expression of IL-17 is upregulated by ischemic stroke and the over-expression of IL-17 indicates a poorer treatment effect and prognosis [5][6][7] . However, IL-17 inhibits autophagy through activating phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K) pathway, one of the most popular pathways to regulate cell proliferation and apoptosis, to interrupt the Glycogen synthase kinase-3β (GSK-3β)-mediated degradation of BCL2 in lung epithelial cells 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Regular aerobic exercise has been known to reduce peripheral inflammation and COX-2 levels [34]; however, the effects of aerobic exercise on COX-2 expression in the brain have not been well investigated. A recent study reported that brain COX-2 levels increased after endurance training, and its expression positively correlated with memory functions [34,35]. In another study, treadmill training was found to have time-dependent up and down regulatory effects on the COX-2 pathway [36].…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, several neurological disorders such as stroke (20, 21) and epilepsy (22, 23), underline the continued interest in targeting these receptors. This also includes an emerging relevance for immunomodulation via actions on peripheral δ-containing receptors or equivalents (24, 25). However, compared to the synaptic γ-containing receptors, pronounced insight into the physiological and pathophysiological role of δ-containing receptors is still limited by the low number of potent and selective compounds.…”
Section: Introductionmentioning
confidence: 99%
“…confirmed the reported selectivity for δ-containing receptors, using δ -/- mice showing that this effect is clearly dependent on the δ-subunit (31). DS2 displays limited brain permeability (31) but was, nonetheless, shown to improve recovery after stroke in mice, plausibly by dampening peripheral immune activation (24). Recently, a methoxy analog of DS2, termed DS2OMe, was identified and confirmed to have a similar potency and subtype selectivity as DS2.…”
Section: Introductionmentioning
confidence: 99%